(A) Being in the City: Performing Arts Walk. Thoughts on a Practice-Based Research Artistic Project of Intervention in the Public Space - Béjar, Marissa (2020)
(A) Being in the City: Performing Arts Walk is a practice-based research project of artistic, performing and interdisciplinary intervention in the streets of Downtown Historic Lima staged in 2018 and 2019. This article shares its conceptual and methodological starting points, centered in the academic discussion about the configuration of the cities and the urban space, in which we take side in the everyday practices and the interactions that they hold, as the axes that configure the city, as well as the performative turn, which values subjectivity in research processes. It also presents this project’s reflexive origin about the being as entity and action, and its research axes that explore dimensions linked to the artistic, performative and knowledge of the city aspects. Finally, it shares the artistic decisions and the creative results to which we arrived.